Komunikasi Efektif sebagai Upaya Penyelesaian Miskomunikasi Jadwal Produksi dan Pengiriman pada Perusahaan Air Mineral Mountoya - Annaba Wulandara; Edza Prasna Anggara; Intan Luthfi Suha Febriyanti; Ummu Arinal Khusna; Wiwiek Rabiatul Adawiyah; Bagas Gumintang; Filda Khoirun Nikmah (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2026)
PT Toyamilindo, a bottled drinking water company operating under the Mountoya brand, faces communication challenges related to production and delivery scheduling. Miscommunication among divisions often leads to production inconsistencies, delivery delays, and reduced operational efficiency. This community service activity aimed to improve employees’ understanding of effective communication as a strategy to enhance coordination and support smoother operational processes. The program was conducted through observation, discussions, training sessions, and assistance in developing communication flow and scheduling formats. Activities involved employees and management representatives through face-to-face interactions. The results showed increased awareness of the importance of clear, timely, and consistent communication in the workplace. Participants gained a better understanding of communication barriers and ways to improve information exchange among divisions. In addition, recommendations regarding communication procedures and work scheduling formats were developed to support daily operations. Effective communication is expected to strengthen internal coordination, minimize information errors, and improve the efficiency of production and delivery activities.=